Steroid hormones in bluegill, a species with male alternative reproductive tactics including female mimicry - Knapp, Rosemary (The Royal Society, 2007)
The proximate mechanisms underlying the evolution and maintenance of within-sex variation in mating behaviour are still poorly understood. Species characterized by alternative reproductive tactics provide ideal opportunities to investigate such mechanisms. Bluegill (Lepomis macrochirus) are noteworthy in this regard because they exhibit two distinct cuckolder (parasitic) morphs (called sneaker and satellite) in addition to the parental males that court females. Here we confirm previous findings that spawning cuckolder and parental males have significantly different levels of testosterone and 11-ketotestosterone. We also report, for the first time, that oestradiol and cortisol levels are higher in cuckolders than in parental males. The two cuckolder morphs did not differ in average levels of any of the four hormones. However, among satellite males which mimic females in appearance and behaviour, there was a strong negative relationship between oestradiol levels and body length, a surrogate for age. This finding suggests that for satellite males, oestradiol dependency of mating behaviour decreases with increasing mating experience. Although such decreased hormone dependence of mating behaviour has been reported in other taxa, our data represent the first suggestion of the relationship in fishes.